Perbandingan Pertumbuhan Fisik antara Murid SD Negeri 92 Kabupaten Sinjai dengan Murid SD Inpres Tabaringan Kota Makassar - Nurliani Nurliani; Hasby Asyhari (Seminar Nasional LP2M UNM, 2017)
Comparison Physical growth between elementary school students 92 Kabupaten Sinjai with elementary school students Inpres Tabaringan Makassar City. This study aims to determine whether there is a difference in physical growth between the Elementary School Students 92 Sinjai with elementary school students Inpres Tabaringan Makassar. This research is a descriptive type of research. The population in this study are students in SD Negeri 92 of Sinjai and Pupils who are in SD Inpres Tabaringan Makassar City which is limited to male gender with age between 10-12 years old. Samples used are students in SD Negeri 92 Kabupaten Sinjai as many as 50 people and students in SD Inpres Tabaringan Makassar as many as 50 students. Sampling technique or sample selection in this research is based on random sampling. Research data in the form of physical growth of both groups are students in SD Negeri 92 Kabupaten Sinjai and Pupils at SD Inpres Tabaringan Kota Makassar analyzed with statistical calculation in the form of: For Descriptive Statistics which include: total value (ΣX), total quadratic value (ΣX2) Average (X) and standard deviation (Sd) will be analyzed directly with the help of computer using SPPS program. The result of this research is there is no real difference in confidence level of 95% physical growth among elementary school students of Inpres Tabaringan of Makassar with elementary school students 92 Kabupaten Sinjai. So it is clear that the environment affects the physical growth of a person. This is due to different environmental conditions and from other factors such as the state of nutrition, economic conditions and patterns of community thinking and sports facilities and infrastructure are available. Kata kunci: Physical growth, elementary school